The transportation act of 1940 - Dewey, Ralph L. (American Economic Review, 1941)
The paper reviews the Transportation Act of 1940 which added water carriers to the list of domestic commercial transportation agencies subject to regulation by the Interstate Commerce Commission (ICC); only airlines remain under separate authority. Railroads, pipelines, motor carriers and water lines are now unified and centralized on a pattern similar to earlier rail statutes. Maximum, minimum, and exact rates and charges of these agencies are now subject to ICC control. This is the first time that a national transportation policy governing all agencies subject to ICC has been enacted. The creation of a temporary Board of Investigation and Research to study the relative economy and fitness of each mode of transportation is another major feature of the Act. Additional responsibilities of the temporary board include: the extent government has subsidized or otherwise aided transportation, the amount of taxes levied upon transportation by all government units, and any other matter likely to lead to improvement of transportation conditions. Numerous changes are also made by the Act in the Interstate Commerce Act, it modifies legislation governing land-grant rate reductions and loans by the Reconstruction Finance Corporation to railroads.